Assessment and impact of dose escalation on anti-drug antibodies in Fabry disease - Lenders, Malte; Brand, Eva (Frontiers in Immunology, 2022)
Enzyme replacement therapy (ERT) with recombinant α-galactosidase A (AGAL) can lead to the formation of neutralizing anti-drug antibodies (ADA), which significantly limit treatment efficacy in patients with Fabry disease (FD). The effects of dose escalation on ADA titer and plasma globotriaosylsphingosine (lyso-Gb3) level are unknown. We screened 250 FD patients (200 males, 50 females) under ERT for ADAs and assessed the impact of an approved dose escalation in affected patients, focusing on ADA titers and plasma lyso-Gb3. ADA-positive patients were identified by serum-mediated inhibition assays, followed by titration assays to determine the individual inhibitory capacities of ADAs against agalsidase-alfa and agalsidase-beta. 70 (35%) of the male patients were ADA-positive, with a mean inhibitory capacity of 83.5±113.7mg AGAL. Although patients receiving agalsidase-beta showed higher inhibitory capacities (84.7±34.7mg) than patients under agalsidase-alfa (60.3±126.7mg, p<0.001), the “theoretical deficit” to the infused dose was lower in patients receiving agalsidase-beta. In seven patients receiving agalsidase-alfa (0.2 mg/kg) ADAs were saturable by switching patients to agalsidase-beta (1.0 mg/kg). The switch resulted in increasing ADA titers within the first months. In 2 out of 7 (28.6%) therapy switchers, dose escalation could lead to durable ADA saturation. Independent of an increase in ADA titers, lyso-Gb3 levels decrease and cardiac and renal parameters remained stable after dose escalation. Dose escalation results in a heterogeneous, unpredictable ADA response, with more than a quarter of all treatment switchers succeeding in ADA saturation. Longitudinal ADA measurements are required to assess the individual risk of affected patients.